Land Bank Agency and Participation of Indigenous Peoples: Where is the Legal Certainty? - Damanik, Pandapotan; Wibowo, Dwi Edi; Agus, Dede; Dubey, Anita Chaturvedi (Faculty of Law, Universitas Jenderal Soedirman, 2023)
This study aims to analyze the problem of legal uncertainty for MHA related to the establishment of a Land Bank as mandated by the Job Creation Perppu. This research is a normative legal research with a conceptual and statutory approach. The results of the study concluded that the obligation to involve the Customary Law Community in land use through the Land Bank agency is said to be urgent, especially in an effort to maintain the mandate of the 1945 Constitution of the Republic of Indonesia and the UUPA to provide guarantees for recognition, protection as well as empowerment of the Indigenous Peoples. Efforts to realize legal certainty for Indigenous Peoples (MHA) in land use through the Land Bank agency with reference to grammatical, authentic, and teleological (sociological) interpretations, it is necessary to expand the meaning of the word